Food plant economics - Maroulis, Zacharias B. , 1957-; Saravacos, George D. , 1928- (Food science and technology, 2008)
Considers the design and economic analysis of food preservation, food manufacturing, and food ingredients plants with regard to a number of representative food processes. This book covers estimations of capital investment and operating costs including statistical data, empirical models, and useful rules of thumb.